Temperature Shocks and Household Savings - Churchill, Sefa Awaworyi; Smyth, Russell; Trinh, Trong-Anh; Yew, Siew Ling (My University, 2022)
We present the first study to examine the impact of temperature shocks on household savings behaviour. We first develop a theoretical model to examine the relationship between average temperature and savings via risk and time preferences. The model predicts an ambiguous effect of both risk and time preferences as channels. We test the theoretical predictions using longitudinal data from the Household, Income and Labour Dynamics in Australia Survey and satellite re-analysis temperature data. We find that a standard deviation increase in average temperature is associated with a 4.3% increase in net worth and a 12.8% increase in savings. We examine risk preferences and time preferences as channels and find that time preferences mediate the relationship between temperature shocks and savings.
Keywords: Housing, communities and neighbourhoods; Income, wealth and finances